PERANCANGAN DAN IMPELEMENTASI SISTEM JADWAL PERKULIAHAN FAKULTAS TEKNIK UNIVERSITAS MUHAMMADIYAH MATARAM BERBASIS WEB - Astutik, Fitri; Rahman, Arif; Idham (Program Studi Informatika Universitas Teknologi Sumbawa, 2025)
Course scheduling is a vital aspect of academic management at the Faculty of Engineering, University of Muhammadiyah Mataram. Currently, the process faces inefficiencies and frequent conflicts between lecturers and students. This study aims to design and implement a web-based information system to optimize scheduling, making it faster and more accurate. The research applies a quantitative approach using the Software Development Life Cycle (SDLC) Waterfall model. The stages include requirement analysis through interviews and observations, system design using UML diagrams and Entity Relationship Diagrams (ERD), implementation with MySQL as the database, and system testing using the Blackbox Testing method. The results show that the system significantly reduces scheduling time from 43 hours to 7 hours in the Civil Engineering study program. However, several issues were identified, such as an excessive number of input columns and the need to re-enter data during scheduling conflicts. For future development, it is recommended to add features showing available rooms and days, as well as allow schedule input via Excel. Usability testing should also be conducted to evaluate system ease of use. The implementation of this system is expected to enhance efficiency and improve the academic experience for lecturers and students alike.